The Bharatiya Nyaya Sanhita, 2023 (BNS) - Ratanlal and Dhirajlal (LexisNexis, 2024)
Ratanlal & Dhirajlal: The Bharatiya Nyaya Sanhita, 2023 is a detailed, section-wise commentary on the BNS which came into effect from 1 July 2024. This comprehensive commentary elucidates the new provisions introduced by the BNS and underscores the changes implemented in the Nyaya Sanhita. Comments after each section provide the corresponding section from the Indian Penal Code, 1860 and highlight the changes brought in along with relevant principles of law and judgments. Key Features: Includes commentary on the Bharatiya Nyaya Sanhita, 2023 – new provisions as well as those retained from the Indian Penal Code, 1860 Contains landmark judgments relevant for interpreting the provisions of the Indian Penal Code, 1860 and the Bharatiya Nyaya Sanhita, 2023, also includes a table on some of the recent judgments Compares relevant provisions of the Indian Penal Code, 1860 with the Bharatiya Nyaya Sanhita, 2023, and vice versa Reflects on the Spirit of the New Criminal Acts with major changes in the Bharatiya Nyaya Sanhita, 2023 Includes Observations/Recommendations of Parliamentary Standing Committee Includes a Table highlighting the section-wise major changes in the Bharatiya Nyaya Sanhita, 2023 Ensures that spirit and essence of the original work is maintained, preserving its relevance and applicability to both the Act and the BNS Related products